A four-quadrant multiplier based on CCII+s - Narksarp, W.; Pawarangkoon, P.; Buakaew, S.; Kiranon, W.; Wardkein, P. (My University, 2010)
This paper presents an analog multiplier based on non-inverting (positive type) second generation current conveyor (CCII+). The proposed circuit can perform as a four-quadrant multiplier. The circuit employs only two positive type second generation current conveyors and two n-channel JFET transistors. The circuit does not require any external passive circuit elements. Simulation results are included to confirm the capability of the circuit with the theory. Moreover, applications of the squarer, frequency doubler and amplitude modulator are demonstrated.